Bovine Mucosal Immune Response to Intranasal Exposure with Live Pasteurella Multocida B:2 - Khin, Myat Nwe (2009)

(untitled)
Haemorrhagic septicaemia (HS) is an infectious disease of cattle and buffalo caused by Pasteurella multocida B:2. It is endemic in most parts of tropical Asia, Africa and India, causing high mortality in livestock and is considered as one of the most economically important livestock diseases in Southeast Asia. Vaccination has been used to control the disease and the oil adjuvant vaccine is most often used although alum precipitate and broth vaccines are also available. Although the available injection vaccines are effective in providing protection, the low vaccination coverage, particularly among cattle and buffaloes kept extensively, is one of the main reasons that lead to disease outbreaks, particularly among those extensively kept, semi-wild cattle and buffaloes. Therefore, the disease remains a significant obstacle to sustainable agriculture in the region and attempts should be made to increase the vaccination coverage. The development of live attenuated vaccine that can be administered intranasally may be an answer. This study reports on the use of an attenuated P. multocida B:2, that has been created by manipulating the gdhA genes, as a component of live haemorrhagic septicaemia vaccine. It is as an alternative way to protect the animals from haemorrhagic septicaemia and in the same time to increase vaccination coverage. The respiratory tract contains an important component of the mucosal immune system, and the first line of immunological defense since it is exposed continuously to inhaled antigens. Intranasal exposures to live wild-type and gdhA derivative of P. multocida B:2 not only successfully stimulated the mucosal immunity of the respiratory tract, but also the systemic immunity. This was evidenced by the increased in the size of BALT, the numbers of lymphocytes, the levels of IgA in the lung lavage fluid and the levels of IgG in the serum of exposed calves. However, the nasal associated lymphoid tissues (NALTs) were successfully stimulated only following intranasal exposures to the wild-type P. multocida B:2. Following intranasal exposures of calves to live gdhA derivative of P. multocida B:2 at 2-week interval and challenged by wild-type P. multocida B:2 four weeks later, the exposed calves were not only able to prevent establishment of infection by wild-type P. multocida B:2 but also produced similar effects in the susceptible commingled calves. When immuno-suppression was created in calves by subcutaneous injections of dexamethasone for 3 consecutive days, and immediately followed by the intranasal exposures to the gdhA derivative of P. multocida B:2, both mucosal and systemic immunities of the immuno-suppressed calves failed to be stimulated. This was obvious when the serum IgA and IgG levels of the exposed, stressed calves were similar to that of unexposed calves. On the other hand, the unstressed calves showed significantly (p<0.05) higher serum IgA and IgG levels following intranasal exposures to the gdhA derivative of P. multocida B:2. Similarly, the IgA and IgG levels in the lung lavage fluid of calves treated with dexamethaosne were significantly (p<0.05) lower than those without dexamethasone treatments. It was concluded that dexamethasone reduced the availability of immune cells, thus reducing immune responses.